Effects of Visual and Auditory Feedback in Violin and Singing Voice Pitch Matching Tasks - Blanco, Angel David; Tassani, Simone; Ramirez, Rafael (Frontiers in Psychology, 2021)
Auditory-guided vocal learning is a mechanism that operates both in humans and other animal species making us capable to imitate arbitrary sounds. Both auditory memories and auditory feedback interact to guide vocal learning. This may explain why it is easier for humans to imitate the pitch of a human voice than the pitch of a synthesized sound. In this study, we compared the effects of two different feedback modalities in learning pitch-matching abilities using a synthesized pure tone in 47 participants with no prior music experience. Participants were divided into three groups: a feedback group (N=15) receiving real-time visual feedback of their pitch as well as knowledge of results; an equal-timbre group (N=17) receiving additional auditory feedback of the target note with a similar timbre to the instrument being used (i.e. violin or human voice); and a control group (N=15) practicing without any feedback or knowledge of results. An additional fourth group of violin experts performed the same task for comparative purposes (N=15). All groups were posteriorly evaluated in a transfer phase. Both experimental groups (i.e. the feedback and equal-timbre groups) improved their intonation abilities with the synthesized sound after receiving feedback. Participants from the equal-timber group seemed as capable as the feedback group of producing the required pitch with the voice after listening to the human voice, but not with the violin (although they also showed improvement). In addition, only participants receiving real-time visual feedback learned and retained in the transfer phase the mapping between the synthesized pitch and its correspondence with the produced vocal or violin pitch. It is suggested that both the effect of an objective external reward, together with the experience of exploring the pitch space with their instrument in an explicit manner, helped participants to understand how to control their pitch production, strengthening their schemas and favoring retention.